OBSTACLES TO THE IMPLEMENTATION OF THE HIV/AIDS CURRICULUM IN GURUVE DISTRICT SECONDARY SCHOOLS IN ZIMBABWE - KASOWE, RITTAH (IJRDO- Journal of Educational Research, 2017)
The aim of this present study was to investigate constraints faced by secondary school teachersin the teaching and learning of HIV/AIDS education in Guruve District in Mashonaland Provinceof Zimbabwe. Specifically, it focused on HIV/AIDS content, evaluation of the subject, teacherqualifications, availability of resources, methodology as well as syllabus interpretation. Thequantitative methodology was used and the descriptive survey design employed. The populationconsisted of all the 840 secondary school teachers in the district. Random sampling was used toselect the 200 respondents. Data were collected using a questionnaire. The study revealed thatteachers were finding it very difficult to discuss sex related issues with children. The study alsorevealed that teachers lacked the knowledge and confidence to teach HIV/AIDS education. Thestudy recommends that teachers should be given proper training in the teaching of HIV/AIDSeducation. There is also need for teachers to be provided with relevant and adequate resources toeffectively guide pupils on this subject.